The Level Of Parental Knowledge About Atopic Dermatitis Disease Is Related To The Incidence Of Recurrence Of Atopic Dermatitis In Children At Haji Medan Hospital - Assyifa, Roihan; Pratiwi, Febrina Dewi (Buletin Farmatera, 2025)
Abstract: Atopic dermatitis is an inflammatory skin disease characterized by recurrent intensive and chronic itching. Atopic dermatitis can occur from childhood to adulthood. This disease is classified as a residual disease, which is a disease that can recur after being declared cured. The recurrence of atopic dermatitis is often caused by the lack of parental knowledge of the causative factors so that it can cause recurrence in the sufferer. This study aims to determine the relationship between the level of parental knowledge about atopic dermatitis disease and the incidence of recurrence of atopic dermatitis in children at Haji Medan Hospital. Data collection in this study used primary data, obtained from respondents by filling out questionnaires that were distributed to parents who had children suffering from atopic dermatitis and came to Haji Hospital Medan for treatment. Questionnaire containing questions related to research titles. Based on the results of the study, there was a relationship between the level of parental knowledge about the recurrence of atopic dermatitis (p = 0.000). The results were obtained that the better the level of parental knowledge, the less likely it is to occur a recurrence of atopic dermatitis in children.